Microscopic techniques of cholesteatoma surgery - Dokoska, M; Tashkovska, E; Marolov, M; Nikolova, S (My University, 2023)
Cholesteatoma of the middle ear or/and mastoid is an erosive process defined by trapped squamous epithelium that produces and accumulates desquamated keratin debris with/without a surrounding inflammatory reaction. Due to its aggressive growth and invasive nature, cholesteatoma tends to cause extracranial and potentially fatal intracranial complications. Otitis media with cholesteatoma is considered an unsafe ear and currently surgery is the definitive line of management with an aim to create a safe and dry ear by exteriorizing the disease and improving hearing. There are different approaches used worldwide and each surgeon has his own beliefs and conceptions/misconceptions. Two main options in cholesteatoma surgery are the canal wall up and canal wall down mastoidectomy. The quest for better surgical outcome has continued to raise challenges and the choice of the surgical technique is always a matter of debate. Hence otologists are in search of a tailored and more adaptable technique. No single method is optimal in all cases of cholesteatoma, so cholesteatoma surgery should be individualized and the choice of the operative procedure based on the extent of the disease and condition of the ME cleft, the needs of the patient, and the surgeon’s experience. Both canal wall–up and canal wall–down mastoidectomies can be utilized successfully in the management of cholesteatomas as long as the operative techniques are performed correctly and appropriate patient selection occurs.
Keywords: cholesteatoma; canal wall-up mastoidectomy; canal wall-down mastoidectomy